2015
DOI: 10.1097/md.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Virologic Response to a Dual Peginterferon alfa-2a and Ribavirin in Treating Chronic hepatitis C Infection

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…We found 36% SVR with the initial pegIFNα2a+RBV regimen (Table 2), similar to previous reports in Mexico of 32.5% (Sandoval-Ramirez et al, 2015). Fifty one percent of the non-cirrhotic patients, and 68% of those with low baseline viral load achieved SVR with pegIFNα2a+RBV (Table 3), similar to other publications (Enomoto & Nishiguchi, 2015;Naing et al, 2015). Diabetes did not associate with failure of pegIFNα2a+RBV treatment: 34.2% of diabetic patients achieved SVR (Table 3), similar to SVR of all the cohort.…”
Section: Discussionsupporting
confidence: 90%
“…We found 36% SVR with the initial pegIFNα2a+RBV regimen (Table 2), similar to previous reports in Mexico of 32.5% (Sandoval-Ramirez et al, 2015). Fifty one percent of the non-cirrhotic patients, and 68% of those with low baseline viral load achieved SVR with pegIFNα2a+RBV (Table 3), similar to other publications (Enomoto & Nishiguchi, 2015;Naing et al, 2015). Diabetes did not associate with failure of pegIFNα2a+RBV treatment: 34.2% of diabetic patients achieved SVR (Table 3), similar to SVR of all the cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, high fibrosis scores did not influence SVR among patients treated with triple combination therapy ( P =.19) (Table ). Historically, 24 or 48 weeks of PEG‐IFN+RBV combination therapy has yielded SVR rates of about 75‐90% across all HCV genotypes in Myanmar . Results from the NEUTRINO study showed SVR rates of 90% after 12 weeks of triple combination therapy for patients with genotypes 1 and 4‐6, and a significantly higher rate of SVR among patients without cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…Direct-acting antiviral (DAA) therapy has high cure rates and a substantially reduced side effects profile compared to dual therapy with pegylated-interferon (peg-IFN) and ribavirin (RBV), and has revolutionized HCV treatment paradigms in many countries[2]. However, DAA treatment is only just beginning to enter the market in Myanmar, leaving peg-IFN and RBV therapy as a viable option[3,4]. …”
Section: Introductionmentioning
confidence: 99%